Investigation of the Lithiation-Trapping of an N-Boc Bispidine-Ketal: Reactivity and Diastereoselectivity - Stead, Darren; O’Brien, Peter; Sanderson, Adam (Synlett, 2015)
The lithiation-trapping of an N-Boc bispidine-ketal using s-BuLi/TMEDA has been studied. Key findings include an activating effect of the 4-ketal group on the lithiation and complete diastereoselectivity with methylation and Cu-mediated allylation. In contrast, reduced diastereoselectivity was noted for direct allylation and silylation; mechanistic explanations are proposed.
Keywords: organolithium reagents; lithiation; stereoselective synthesis; diastereoselectivity; bispidines